The Impact of Cognitive Intervention on the Cognition of Adults Over 50 with Mild Cognitive Impairment (MCI) in Asia: A Systematic Review - Aziz, Nor Afifah; Subramaniam, Ponnusamy; Ghazali, Shazli Ezzat; Mustafa, Wani Amira (IIUM Medical Journal Malaysia, 2022)
The cognitive intervention for the ageing population is growing rapidly. This review aimed to explore the impact of cognitive intervention on the cognitive abilities among adults over 50 with mild cognitive impairment (MCI) in Asia. Articles on randomised controlled trials (RCT) studies published between 2010 and December 2020 in PubMed, Science Direct, Web of Science, and Scopus databases were searched. A total of 13 studies were included in this review for further analysis. The results showed that cognitive training can be effective in improving the cognitive function in adults with MCI in various aspects, including memory, attention, executive functioning, reducing subjective memory complaints, and improving daily living skills. The findings indicated that different modalities of cognitive intervention, namely single-domain, multi-domain, and multimodal modalities could be a promising intervention in improving the overall cognitive abilities of adults with MCI in Asia. The single-domain cognitive intervention was influenced by the far transfer effect that improved other untrained cognitive areas. Both multi-domain and multimodal cognitive interventions showed improvement in the global cognitive function and transfer effect on the non-cognitive areas such as daily activities and mood. Future review could explore the impact of intervention duration on cognitive abilities and the transfer effect for each modality to understand the ideal intervention package for adults over 50 with MCI in Asia.